Periodic fever syndromes: beyond the single gene paradigm - Clara Westwell-Roper; Iwona Niemietz; Lori B. Tucker; Kelly L. Brown (BMC, 2019)
Abstract Familial Mediterranean fever (FMF) is the most common monogenic autoinflammatory disease in Canada and is characterized by a clinical syndrome of episodic inflammatory symptoms. Traditionally, the disease is defined by autosomal recessive inheritance of MEFV gene variants, yet FMF also not uncommonly manifests in individuals with only one identified disease-associated allele. Increasing availability and affordability of gene sequencing has led to the identification of multiple MEFV variants; however, they are often of unknown clinical significance. Variants in other genes affecting overlapping or distinct inflammatory signaling pathways - together with gene-environment interactions including epigenetic modulation - likely underlie the significant genetic and phenotypic heterogeneity seen among patients with this disease. We review recent evidence of the expanding spectrum of FMF genotype and phenotype and suggest that current drug funding schemes restricting biologic agents to patients with homozygous mutations have not kept pace with our biological understanding of the disease.